Wood-lignin: Supply, extraction processes and use as bio-based material. (March 2019) - Tribot, Amélie; Amer, Ghenima; Abdou Alio, Maarouf; de Baynast, Hélène; Delattre, Cédric; Pons, Agnès; Mathias, Jean-Denis; Callois, Jean-Marc; Vial, Christophe; Michaud, Philippe; Dussap, Claude-Gilles
Graphical abstract: Abstract: Wood is the main source of lignin in the world. This generic term "Lignin" describes a large group of aromatic biopolymers, i.e. the second most abundant class of biopolymers on Earth. It accounts for approximately 30% of wood weight while conferring rigidity and antimicrobial properties to wood. Since lignin is combined with cellulose and hemicellulose in biomass, this will constitute a limiting factor in the bioconversion of wood into pulp or second-generation biofuels through the biochemical pathway. These processes generate a huge quantity of lignin as by-products, mainly used as fuels for energy savings. Recently, alternative routes towards lignin's valorization were emphasized (e.g. as bio-based resins, adhesives, or composites), but they strongly depend on lignin's chemical structure, also dependent on fractionation process. Therefore, this review aims to summarize the strong interplay between extraction processes, resource supply, and recent uses of lignin into bio-based materials.